KEDUDUKAN HUKUM SURAT EDARAN MAHKAMAH AGUNG (SEMA) NOMOR 2 TAHUN 2023 TENTANG PERKAWINAN BEDA AGAMA - Delian Adlofeno (Faculty of Law, University of Mataram, 2026)
Interfaith marriage has long been an issue in Indonesia, given the country's cultural diversity, particularly in the aspect of religion. Article 2, paragraph (1) of Law Number 1 of 1974 concerning Marriage stipulates that a marriage is valid if it is performed according to the laws of each party's respective religion and beliefs. Another provision, Law Number 23 of 2006 concerning Population Administration, in the Elucidation of Article 35 letter (a), states that